Therapeutic drumming: Cure for physical, mental and social ailments / Ahmad Danial Ahmad Maliki - Ahmad Maliki, Ahmad Danial (2013)
This research presents the use of therapeutic drumming as an effective, less risky intervention designed as a complementary method in healing physical, mental, and social ailments. Therapeutic drumming has demonstrated effectiveness in reducing physical pain, decreasing anxiety, and increasing relaxation. In addition, therapeutic drumming has been used as a method that can help in reducing social issues. This research will look in-depth at how therapeutic drumming can be a cure for physical, mental, and social ailments, the methods used in therapeutic drumming, and also the comparisons between therapeutic drumming and the conventional methods for curing such ailments.